Eukaryotic Cell Capture by Amplified Magnetic in situ Hybridization Using Yeast as a Model - Bastian, Fabiola; Melayah, Delphine; Hugoni, Mylène; Dempsey, Nora M.; Simonet, Pascal; Frenea-Robin, Marie; Fraissinet-Tachet, Laurence (Frontiers in Microbiology, 2021)
A non-destructive approach based on magnetic in situ hybridization (MISH) and hybridization chain reaction (HCR) for the specific capture of eukaryotic cells has been developed. As a prerequisite, a HCR-MISH procedure initially used for tracking bacterial cells was here adapted for the first time to target eukaryotic cells using a universal eukaryotic probe, Euk-516R. Following labelling with superparamagnetic nanoparticles, cells from the model eukaryotic microorganism Saccharomyces cerevisiae were hybridized and isolated on a micro-magnet array. In addition, the eukaryotic cells were successfully targeted in an artificial mixture comprising bacterial cells, thus providing evidence that HCR-MISH is a promising technology to use for specific microeukaryote capture in complex microbial communities allowing their further morphological characterization. This new study opens great opportunities in ecological sciences, thus allowing the detection of specific cells in more complex cellular mixtures in the near future.